NARRATIVE CHALLENGES AND METAFICTIONAL AWARENESS IN POSTMODERN LITERATURE: READING ALI SMITH’S "THE WHOLE STORY AND OTHER STORIES" - Locatelli, Angela (Armenian Folia Anglistika, 2022)
One of the widespread features of the literary postmodern, and one of its most relevant aspects in epistemic terms, is the foregrounding of the narrative dimension and the problematizing of “facts”. These narratological elements are both influenced by, and have an impact on, contemporary notions of subjectivity and reality.One of the widespread features of the literary postmodern, and one of its most relevant aspects in epistemic terms, is the foregrounding of the narrative dimension and the problematizing of “facts”. These narratological elements are both influenced by, and have an impact on contemporary notions of subjectivity and reality. In postmodern literature the “factuality” of the story is made questionable from different angles, and this is due to several aesthetic and stylistic elements which will be discussed with reference to Ali Smith’s collection of short stories The Whole Story and Other Stories (2004). This is an exemplary text of the literary postmodern, since it represents a unique instance of the dissolution of “factualities”, in which metafiction plays a relevant role. “Facts” in these stories are improbable, suspended, and indeterminate due to a narrative strategy which routinely questions “events” and/or exposes their epistemological constructedness. Readers of these short stories are not only trained into an awareness of metafiction as a major component of the narration, but they are also often left in a state of bewilderment leading to a more or less amused disbelief, or to a profound epistemological questioning.
Keywords: The Literary Postmodern; metafiction; unreliability; “facts” in fiction; fabrication of truth; forms of fabulation; fluid subjectivities